(untitled) (Journal of Management and Social Sciences, 2021)
The role of women in nation building cannot be over-emphasized. In any nation, women’s contribution to development is significant in the area of culture, economy and politics. Religion has been a strong influence on how women participate in society. With this, the impact has been both positive and negative. In national development discourse, little attention is paid to the influence of religion on women and how they participate in national development. In filling this scholarly gap, this paper gives an overview of religion and development in Nigeria. It examines African traditional religion and women participation in Nigeria, the new religions and women participation in Nigeria. It further discusses women’s contribution to national development. This paper adopts Emile Durkheim’s functionalism theory of religion. Data is collected from secondary sources such as books, journals and articles. Recommendations are made towards making women do more in contributing to national development. Keywords Religion, women, national development